Uremic Toxins Elimination from Simulated Intestinal Serum with Mesoporous Silica Nanoparticles Coupled with Molecularly Imprinted Polymers and Amino Linker - Miardan, Leila Nazmi; Rezaii, Ebrahim; Mahkam, Mehrdad; Khosroshahi, Hamid Tayebi (Current Organic Synthesis, 2025)
BackgroundOne of the most researched issues is the elimination of uremic toxins from the human body. These toxins can build up and lead to catastrophic issues including renal failure. To get rid of them, absorbents like activated carbon, zeolites, and other minerals are frequently utilized.MethodsMesoporous silica nanoparticles functionalized with (3-Aminopropyl) triethoxysilane (APTES) linker (MSN-NH2) and mesoporous silica nanoparticles grafted with molecularly imprinted polymers (MSN-MIP) from the previous study were examined in this study to determine how well they absorbed urea, creatinine, and uric acid in a simulated intestinal serum.ResultsMSN-MIP's large surface area (879.12 (m2/g)) and volume of pores (0.8475 (cm3/g)) made removal results that were satisfactory in the simulated serum. Additionally, MSN-MIP demonstrated a high urea adsorption capacity (qm = 1836.45 mg/g). Creatinine (qm = 1529.5 mg/g) and uric acid (qm = 1210.6 mg/g) were absorbed via NH-MSN2, which demonstrated a noticeable potential for absorption. The results of cell viability test for the first 72 hours, showed that the use of these absorbents in hemodialysis systems is acceptable.ConclusionSynthesized adsorbents can be utilized in the hemodialysis system since the results of the cell viability test also showed that the percentage of cell viability was extremely high up to 72 hours.
Keywords: Renal failure